The Determination of Drying Behavior of Enriched Izmir Gevrek with Protein - Gülsüm Merve Turkut; Hülya Çakmak; Şebnem Tavman (Pamukkale University Journal of Engineering Sciences, 2015)
In this study, Izmir gevrek -highly consumed at the breakfasts- was enriched with dairy proteins by using dairy products (Izmir tulum cheese, milk powder and whey powder)at different levels and 5 mm thick disc-shaped sliced gevrek was dried at three different temperatures (140, 150 and 160°C) in a convection oven. The drying characteristics of snacks were examined with six different thin-layer drying models that are commonly used in literature. The Page model gave a better fit to experimental drying data and had the highest adjusted R-square with the lowest reduced chi-square and root mean square error values as compared to other models. The effective diffusion coefficient was calculated and the activation energy was derived from Arrhenius equation.